2007
DOI: 10.1002/cmdc.200600262
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory CpG Oligonucleotides Form Defined Three‐Dimensional Structures: Results from an NMR Study

Abstract: The DNA eicosamer 5'-TCCATGACGTTCCTGATGCT-3' is known to stimulate the innate immune system of vertebrae. The immunostimulatory activity is based on the activation of Toll-like receptor 9 (TLR9). While it is known that the CG dinucleotide of the eicosamer has to be unmethylated, the structural basis of the recognition of the DNA through the receptor remains unclear. Oligodeoxynucleotides containing the sequence of the eicosamer, or a portion thereof, ranging in length from hexamer to pentaeicosamer were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 81 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…However, the most efficient murine CpG-ODN contain the CG dinucleotide sequence within a self-complementary motif. Moreover, recent results using NMR spectroscopy indeed confirm partial duplex formation of minimal CpG-ODN (He et al, 2007).…”
Section: Recognition Of Cpg-odn: Single-stranded or Double-stranded?mentioning
confidence: 67%
See 1 more Smart Citation
“…However, the most efficient murine CpG-ODN contain the CG dinucleotide sequence within a self-complementary motif. Moreover, recent results using NMR spectroscopy indeed confirm partial duplex formation of minimal CpG-ODN (He et al, 2007).…”
Section: Recognition Of Cpg-odn: Single-stranded or Double-stranded?mentioning
confidence: 67%
“…Furthermore, duplex recognition is also favored due to thermodynamic reasons. This hypothesis of duplex recognition, which has been substantiated by us in different ways, has enabled us to design multiple new ODN with TLR9 activity (Narayanan et al, 2003;He et al, 2007).…”
Section: Recognition Of Cpg-odn: Single-stranded or Double-stranded?mentioning
confidence: 87%
“…The major groove is the site most frequently involved in sequence-specific recognition of DNA by proteins (31). Duplex-forming potential is known to affect RNAi and the structural characteristics of certain immunostimulatory CpG oligonucleotides (32). Thymidine and 5-methylcytidine are sterically more demanding, and 7-deazaguanosine lacks N7 as a hydrogen bond acceptor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The following can be stated without any doubts, however: 1) compound 1 does show signs of structure formation in its UV-melting curve, 2) the low temperature transition in this curve is significantly reduced for 1dT, and 3) uridine residues are involved in forming base pairs in all sequences evaluated with structure prediction algorithms thus far. Because defined three-dimensional structures are advantageous for selective molecular recognition (32), this finding may not be accidental.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affecting of the ability of CpG ODNs to function as TLR9 ligands have been reported (Yi et al, 1998;Hartmann and Krieg, 2000;Hartmann et al, 2003). For example, early studies showed that a species-specific difference in optimal CpG motif sequences with GTCGTT being optimal for human (Bauer et al, 2001) and GACGTT being optimal for mice (He et al, 2007). The immunostimulatory efficiency of CpG motifs is enhanced by the number and spacing of CpG motifs.…”
Section: Development Of a Computer Program For Constructing An Electrmentioning
confidence: 96%